2019
DOI: 10.1097/iae.0000000000002231
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effects of Vital Dyes After Uneventful Vitreomacular Surgery

Abstract: Our rather homogeneous study showed no significant difference between both dyes. Thousand five hundred patients would need to be examined to find a significant difference in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Comparable postoperative findings have, to our knowledge, never been observed before the introduction of acid violet 17 into vitreoretinal surgery, or after withdrawal of the dye from the market. According to our knowledge, a similar observation after the use of this dye was only reported by Röhrig et al [5] in an eye after macular hole surgery. Since the dye was only on the market for a very short time, very few clinical reports are available on postoperative findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Comparable postoperative findings have, to our knowledge, never been observed before the introduction of acid violet 17 into vitreoretinal surgery, or after withdrawal of the dye from the market. According to our knowledge, a similar observation after the use of this dye was only reported by Röhrig et al [5] in an eye after macular hole surgery. Since the dye was only on the market for a very short time, very few clinical reports are available on postoperative findings.…”
Section: Discussionsupporting
confidence: 83%
“…this mode of application is different from the label and the way primed by the delivered equipment in the dye package. Röhrig et al [5] retrospectively compared the outcome in patients after macular hole surgery with the use of either Membrane Blue-Dual (DORC, Zuidland, Netherlands) or ala purple. The authors observed an insignificant trend of worse average visual acuity, and more eyes with a postoperative loss of more than 2 lines in the acid violet 17 group.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the use of vital dyes in vitreoretinal surgery is very common and represents an important tool during the surgical procedure. Vital dyes, for their defined mechanism of action, are not supposed to damage the stained cells, however, in the past, some concerns about potential retinal toxicity has been raised (Röhrig et al, 2019). Awareness about vital dyes safety was mainly related to dye uptake and retention in retinal layers, underneath to the ILM (Cheng et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of our study are the small sample size and a relatively short follow-up time, which may have led to insufficient statistical analysis. Recently it has been shown that a sample size of more than 1000 would be required to detect subtle negative effects of a vital dye [29]. However, it is in the best interest of vitreoretinal surgeons to have real life safety data early on to improve patient safety.…”
Section: Discussionmentioning
confidence: 99%